Colonic acute malignant obstructions: effectiveness of self-expanding metallic stent as bridge to surgery - Pierluigi Consolo; Giuseppa Giacobbe; Marcello Cintolo; Andrea Tortora; Fausto Famà; Maria Gioffrè-Florio; Socrate Pallio (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Bowel obstruction is a frequent event in patients with adenocarcinoma, affecting, in some series, almost one-third of the patients. In the last decades, in addition to surgery, self-expanding metallic stents (SEMSs) are available both as a bridge to surgery (BTS) or palliation. The aim of our study was to demonstrate the safety and efficacy of the use of SEMSs as BTS in selected patients with acute colonic malignant obstructions. Materials and Methods: In total, 125 patients with malignant colonic obstruction who underwent emergency surgery or stent insertion were retrospectively enrolled in our study; 62 patients underwent surgery initially, whereas 62 were subjected to stenting as BTS. The 6-month and 1-year survival rates after the procedure (stenting or surgery) and short-term and long-term complication rates were considered as primary endpoints; the recanalization rate after Hartmann’s procedure and the length of hospitalization were considered as secondary endpoints. Results: On comparing the surgery group (SG) and the BTS group (BG), we observed a lower short-term complication rate (p<0.05) and a reduction in the mean hospital stay (16.1±7.7 vs. 13.5±3.0, p<0.05) in the latter. No differences in long-term complications were found. The recanalization rate after Hartmann’s procedure was higher in BG than in SG, although this was not statistically significant. Conclusion: Our experience shows that SEMS insertion is a safe and effective technique in selected patients with colonic malignant obstruction; the reduction in hospital stay and short-term complications in BG is an important cost-saving aim.